Pengaruh Kebiasaan Refleksi Harian terhadap Pembentukan Karakter Mahasiswa STP Dian Mandala Gunungsitoli - Marbun, Martina Rosmaulina (Jurnal Magistra, 2025)
Daily reflection is one of the spiritual traditions in Catholic teaching that aims to reassess daily actions in the light of faith. This study discusses the influence of daily reflection habits on the formation of Catholic students' character, especially in terms of honesty, discipline, empathy, and responsibility. The research was conducted with a descriptive qualitative approach through in-depth interviews with Catholic students from various universities in Indonesia. The results of the study show that daily reflection not only strengthens a personal relationship with God, but also fosters moral awareness that is the basis for character formation. Thus, daily reflection can be seen as a spiritual habit that has a real impact on the formation of an academic culture of integrity.